Indicadores de qualidade de Plintossolo e relação com a produtividade do milho sob plantio direto em aléias - Martins, Alba Leonor da Silva (2006)
The slash and burn is practiced in Maranhao State, Brazil, which soils are affected by adverse climate conditions, as continuous cycles of rigorous rain and drought, with many problems of impeditive layers, superficial crust and, consequently, bad draining, affecting crops. In that conditions it was implanted on rural settlement area, in 2002, an alternative system, alley cropping with Clitoria fairchildiana, an leguminous. In that system, annually the leguminous are pruned, and its branches put on soil to maintain the covering of surface. In 2005, the maize was planted in no-tillage system. The aim of this study was to determine the chemical and physical quality indicators of the Plinthosols. The area of experiment was marked, using 44 lines of leguminous, forming grids of 10x10m, beginning in the center of leguminous, in joint the maize rows. All the grid points were geoferrered in cartesian plan, performing 113 points. The sample was “square grid” mode. The chemical indicators were phosphorus, potassium, calcium, magnesium, potential acidity, organic carbon and pH in KCl and the physical were bulk density, total porosity, aeration capacity and water superficial permeation capacity by Guelph permeameter method. Preliminarly the indicators were analysed by descriptive statistic and after, by geostatistic. Chemical indicators were more relevant to affect the maize productivity than physical indicators. Among the soil physical indicators the superficial permeation was the more influenced maize productivity. Although the bulk density was high, (higher than 1,4g.cm-3), didn’t affect that much the maize productivity. Geostatistic revealed as an useful instrument, better than descriptive statistic, to show indicators variability and to show better form in case to adopt new practice of cultivation.